Interhemispheric Approach - Anetsberger, Stephanie; Gonzalez- Lopez, Pablo; Elsawaf , Yasmeen; Giotta Lucifero, Alice; Luzzi, Sabino; Elbabaa , Samer (Acta Biomedica Atenei Parmensis, 2022)
The interhemispheric approach is the natural route to reach the parafalcine and paraventricular structures through the interhemispheric fissure.In this chapter, we report the main anterior and posterior corridors of the interhemispheric approach.